Analysis of financial convergence between the BRICS and OECD countries - Nasim Iranmanesh (PLoS ONE, 2025)
Financial convergence is a process for establishing a relationship among the financial markets of different countries; as a result of such process the rates of similar financial assets in different markets and countries become very close to each other. Some factors might create financial convergence. of which the trade and international capital flows among countries, the presence of banks and other financial institutions in the international arena, the availability of clear and accurate information of markets and financial organizations, and the existence of similar infrastructure and their characteristics from economic, legal and cultural perspectives can be mentioned. The issue of financial convergence with the aim of achieving global financial markets and taking advantage of its capabilities and characteristics would be very important for all countries, especially the emerging countries. This study examines financial convergence in the money and capital markets of the Organization for Economic Co-operation and Development (OECD) and BRICS countries in the period of 2007–2020. The study utilizes the Panel Convergence Methodology and Cluster Analysis (Philips and Sul methodology) along with a clustering algorithm. The findings indicate a lack of overall convergence between OECD and BRICS countries in both financial markets (money and capital) this is due to the lack of similar economic infrastructure, differences in the size of the economy, and variations in trade, financial and monetary freedom indicators, trade relations, and capital transfers. The cluster test in the money market confirms the existence of 3 convergence clubs among the studied countries. The convergence of emerging BRICS countries in the money market, with a large number of OECD developed countries, is a confirmation of the development of their banking sector in the recent years. On the other hand, the capital market survey also shows the presence of 5 convergence clubs between OECD and BRICS countries. Besides, it’s been shown that South Africa, along with Lithuania, Turkey, Slovakia and Latvia, has established a divergent group.